Development and phenotypic characterization of a native Theobroma cacao L. germplasm bank from the Loreto region of the Peruvian Amazon: Implications for ex situ conservation and genetic improvement - Imán Correa, Sixto Alfredo (2025)
Introduction: The ex situ conservation and characterization of native Theobroma cacao L. genetic resources are critical for sustainable cacao production and breeding programs in the face of climate change and escalating disease pressures. This study aimed to establish and characterize a novel germplasm bank from the Loreto region of the Peruvian Amazon, a key center of cacao diversity. Methods: We collected 140 native cacao accessions across 15 river basins in eight provinces of the Loreto region. Accessions were propagated using optimized grafting techniques with IMC 67 rootstock. Phenotypic evaluation was conducted on 402 plants using 36 standardized descriptors (25 quantitative and 11 qualitative). Data analysis included multivariate analysis using Uniform Manifold Approximation and Projection (UMAP) and Shannon-Weaver diversity indices to assess morphological diversity patterns. Results: Grafting achieved 100% survival rate, establishing a comprehensive germplasm bank. Phenotypic characterization revealed exceptional morphological diversity, with quantitative traits exhibiting substantial variation, particularly in fruit characteristics (CV = 15.82–50.82%) and pod index (CV = 144.82%). Multivariate analysis identified five distinct phenotypic groups, with reproductive traits showing stronger differentiation than vegetative traits. Shannon-Weaver diversity indices highlighted high overall phenotypic diversity (H' ≈ 0.7), with seed longitudinal shape and fruit apex form displaying the highest trait-specific diversity (H' > 1.0). Conclusion: This comprehensive characterization establishes a foundation for future multiomics studies and advanced breeding strategies. The documented diversity offers opportunities to leverage CRISPR-Cas-based editing and omics technologies to develop climate-resilient, high-yielding cacao varieties with superior quality traits, contributing significantly to global cacao conservation and improvement programs.